Tingkat Kesukaan Rusa Bawean (Axis kuhlii) terhadap Jenis-Jenis Tumbuhan Bawah di Suaka Margasatwa dan Cagar Alam Pulau Bawean - Sena Adi Subrata; Muhammad Faddel Jauhar (Jurnal Ilmu Kehutanan, 2007)
Level of Food Preference of Bawean Deer (Axis kuhlii) on Food Species in Wildlife Sanctuary and Nature Reserve of Bawean IslandThis research has a background on the importance of food preference of Rusa Bawean (Axis kuhlii). This information can be used to ensure the adequacy of preferred food availability within their habitat. This paper aimed to estimate food preference of Rusa Bawean employing faecal analysis. The technique was selected because it is safe for the animal and is easy in data analysis and interpretation. To achieve the aim, quasi experimental design was applied to 30 vegetation plots and 60 faecal samples. Data was collected during January 2005 and June 2006 in the area of Wildlife Sanctuary and Nature Reserve of Bawean Island. Data was analyzed with chi-square test and food selection index. Result shows Rusa Bawean have preferences on some of food species, and they do not select their food species randomly according to its abundance.  Preferred food species include Kabak-kabakan alas (Brachiaria distachya), Talioar (Panicum cordayum), Gadung (Dioscorea hispida), Andudur (Caryota mitis), Rombok putih (Merremia peltata), Pele (Urena lobata) and Kabak-kabakan merah (Ischaemum timorense). Whereas avoided food species include Lating-latingan (Scleria hebecarpa), Ancucu (Pericampylus glaucus), Lambu Merah (Paspalum conjugatum), Alang-alang (Imperata cylindrica), Padi-padian (Centotheca lappacea), Lente-lentean (Fimbristylis dichotoma), Taliata (Lygodium circinnatum ) dan Kayu sape (Symplocos adenophylla).